Hydrolysis capacity of different sized granules in a full-scale aerobic granular sludge (AGS) reactor. (1st August 2022) - Toja Ortega, Sara; van den Berg, Lenno; Pronk, Mario; de Kreuk, Merle K.
Highlights: Aerobic granules of different sizes exhibit similar surface-specific hydrolysis. Aerobic granules of different sizes differ in their microbial community composition. Activity staining and FISH are combined to characterize hydrolysis sites. Hydrolysis of influent polymers mainly occurs in the outer layer of aerobic granules (<100 µm depth). PAOs and GAOs are located nearby hydrolysis sites. Abstract: In aerobic granular sludge (AGS) reactors, granules of different sizes coexist in a single reactor. Their differences in settling behaviour cause stratification in the settled granule bed. In combination with substrate concentration gradients over the reactor height during the anaerobic plug-flow feeding regime, this can result in functional differences between granule sizes. In this study, we compared the hydrolytic activity in granules of 4 size ranges (between 0.5 and 4.8 mm diameter) collected from a full-scale AGS installation. Protease and amylase activities were quantified through fluorescent activity assays. To visualise where the hydrolytic active zones were located within the granules, the hydrolysis sites were visualized microscopically after incubating intact and sliced granules with fluorescent casein and starch. The microbial community was studied using fluorescent in situ hybridization (FISH) and sequencing. The results of these assays indicated that hydrolytic capacity was present throughout the granules, but the hydrolysis of bulk substrates was restricted to the outer 100 µm, approximately. Many of the microorganisms studied by FISH, such as polyphosphate and glycogen accumulating organisms (PAO and GAO), were abundant in the vicinity of the hydrolytically active sites. The biomass-specific hydrolysis rate depended mainly on the available granule surface area, suggesting that different sized granules are not differentiated in terms of hydrolytic capacity. Thus, the substrate concentration gradients that are present during the anaerobic feeding in AGS reactors do not seem to affect hydrolytic activity at the granule surfaces. In this paper, we discuss the possible reasons for this and reflect about the implications for AGS technology. Graphical abstract: Image, graphical abstract